2013
DOI: 10.1123/japa.21.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses During Downhill Treadmill Walking at Self-Selected Intensity in Older Adults

Abstract: Cardiovascular responses of older adults to downhill (DTW, -10% incline) and level treadmill walking (0%) at self-selected walking speed (SSWS) were examined. Fifteen participants (age 68 ± 4 yr, height 1.69 ± 0.08 m, body mass 74.7 ± 8.1 kg) completed two 15-min walks at their SSWS (4.6 ± 0.6 km/hr). Cardiovascular responses were estimated using an arterial-volume finger clamp and infrared plethysmography. Oxygen consumption was 25% lower during DTW and associated with lower values for stroke volume (9.9 ml/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
2
22
4
Order By: Relevance
“…A recent study has reported that downhill walk resulted in an increased total peripheral resistance and hence DBP, compared to level walking. [11] However, comparison of the DBP after an uphill walk to that of a downhill walk yielded a statistically non-significant result in the present study. In addition, compared to some of the previous studies, [11,15] accentuated HR and slightly lower SBP response was obtained in our study.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…A recent study has reported that downhill walk resulted in an increased total peripheral resistance and hence DBP, compared to level walking. [11] However, comparison of the DBP after an uphill walk to that of a downhill walk yielded a statistically non-significant result in the present study. In addition, compared to some of the previous studies, [11,15] accentuated HR and slightly lower SBP response was obtained in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…[11] However, comparison of the DBP after an uphill walk to that of a downhill walk yielded a statistically non-significant result in the present study. In addition, compared to some of the previous studies, [11,15] accentuated HR and slightly lower SBP response was obtained in our study. "Cardiovascular drift" phenomenon can explain the variation in HR, SBP, and DBP reported in our result.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The downhill exercise damages more muscle than concentric exercise, but it produces a greater muscle force and muscle growth factors in ageing (Gault et al . ; Mueller et al . ).…”
Section: Discussionmentioning
confidence: 99%